Features of the clinic in patients with non-tumor mechanical jaundice with concomitant pathology - V. E. Fedorov; B. S. Kharitonov; V. V. Maslyakov; A. D. Aslanov; O. E. Logvina; M. A. Narizhnaya (Вестник хирургии имени И.И. Грекова, 2021)
The Objective was to improve the results of diagnostics of the severity of patients with complications of cholelithiasis, occurring in the form of mechanical jaundice, against the background of comorbidity.Methods and Materials. 537 patients admitted in the clinic of hospital surgery of Kabardino-Balkar State University named after H. M. Berbekov in the period from 2010 to 2019 were examined. The terms of admission to the hospital were different. 25 (4.6 %) people were admitted in a short period of time up to 6 hours. A day after the onset of the disease – 82 (15.3 %) people. More than half – 277 (51.6 %) people were hospitalized a week after the onset of the disease. We analyzed the data of comorbidity scales of CIRS, Kaplan–Feinstein and Mary Charlson Index, as well as biochemical criteria reflecting the severity of calculous cholecystitis, jaundice and concomitant diseases.Results. As a result of their analysis and comparison, we found that comorbidity in patients of this kind is the main aggravating factor and worsens the пeneral condition as the stages of jaundice develop.Conclusion. We found out that a common biochemical tests as for characterizing changes of the hepatocyte in nontumor obstructive jaundice, and for evaluating the degree of impact of comorbidity are the content of blood alkaline phosphatase, creatine phosphokinase and transaminases. Intoxication syndrome in patients with cholangitis and comorbidity so negatively affect all organs and systems of the body that it can lead to inoperability.